Better means more: property rights and high-growth aspiration entrepreneurship - Saul Estrin; Julia Korosteleva; Tomasz Mickiewicz (Institute for the Study of Labor (IZA), 2009)
This paper contrasts the determinants of entrepreneurial entry and high-growth aspiration entrepreneurship. Using the Global Entrepreneurship Monitor (GEM) surveys for 42 countries over the period 1998-2005, we analyse how institutional environment and entrepreneurial characteristics affect individual decisions to become entrepreneurs and aspirations to set up high-growth ventures. We find that institutions exert different effects on entrepreneurial entry and on the individual choice to launch high-growth aspiration projects. In particular, a strong property rights system is important for high-growth aspiration entrepreneurship, but has less pronounced effects for entrepreneurial entry. The availability of finance and the fiscal burden matter for both.
urn:nbn:de:101:1-20091009976
Keywords: D23; D84; G21; J23; J24; K11; L26; P51; 330; High-growth aspiration entrepreneurship; entrepreneurship; start-ups; property rights; Unternehmer; Berufswahl; Unternehmensgründung; Innovation; Unternehmenswachstum; Institutionelle Infrastruktur; Eigentumsrecht; Welt